Penerapan Teknik Pengambilan Gambar pada Produksi Video Feature “Tangan Kecil, Pena Besar” - Anggi Talisa Permatasari Siahaan; Kokom Komariah; Gumgum Gumilar (BADAN PENERBIT STIEPARI PRESS, 2025)
A feature video is an audiovisual work designed to convey information through a narrative and emotional approach. In this final project, the author highlights the issue of education for street children through a feature video titled